(untitled) (Olhares, 2025)
This research is linked to the field of cultural mediation, aesthetic reception, and cultural citizenship, focusing on the construction of a scenic-literary show in the city of Marabá, Pará. I describe the construction of the performance soiree The Guests, reflecting on the confluence between the aesthetics of the scene and the ethics of its backstage, based on affectivity as a mobilizing force that seeks to build horizontality in interpersonal and institutional relationships. This process culminates in a scenic experience in which artists and audiences act in co-authorship. It reveals identity facets of the researched territory, highlighting that the mediation process uses particular tactics to win over each of the guests.